CONTRIBUTION OF GREEN PRODUCT AND CONSUMER REPURCHASE INTENTION - Erisa Aprilia Wicaksari; Bogy Febriatmoko (Journal of Research in Social Science and Humanities, 2024)
Samsung is a well-known global trademark, its products are used all over the world. In the midst of global environmental pollution issues, it is interesting to research this product because Samsung declares its products to be environmentally friendly. Worrying environmental conditions also occur in Indonesia, so it is necessary to research the role of this product in preserving the environment in Indonesia with the topic of consumer behavior, namely interest in repurchasing Samsung products. There are five hypotheses in this research, namely, Product Quality has a positive influence on Repurchase Intention, Product Quality has a positive influence on Consumer Satisfaction, Green Product has a positive influence on Consumer Satisfaction, Green Product has a positive influence on Repurchase Intention, Consumer Satisfaction has a positive influence on Repurchase Intention . The method used in this research is quantitative with structural equation modeling (SEM) analysis tools. The results obtained in this research are that improving product quality will increase consumer satisfaction and Samsung needs to do this to increase purchasing interest in its products